Pendidikan Multikultural dalam Rangka Memperkuat Kewaspadaan Nasional Menghadapi Ancaman Radikalisme di Indonesia - Hikam, Muhammad AS (UI Scholars Hub, 2018)
Multicultural education is a set of strategies to strengthen national integration aimed at facing possible threat to national security. Multiculturalism reflects Indonesia's socio-political realities due to the existing ethnic and cultural background of the nation. The diversity is both a priceless wealth and, at the same time, a potential threat factor that could endanger Indonesia's national security. Therefore, the government needs a breakthrough by implementing and strengthening its national vigilance among Indonesian people through multicultural education. The latter would widen and deepen the people's understanding of diversities that exist in society as well as enforce a sense of belongingness and solidarity. The implementation of multicultural education must be a join effort of government and the civil society in the forms of formal, informal, and non formal curricula.